Factors Associated with Re-attendance at Emergency Departments Among Older Adults: A Cross-Sectional Analytical Study - Saengdao Janda; Juree Sansuk (Inquiry: The Journal of Health Care Organization, Provision, and Financing)
Emergency department (ED) re-attendance among older adults is an increasing global concern, often reflecting gaps in chronic disease management, discharge planning, and continuity of care. This study aimed to determine the frequency of ED re-attendance and identify associated patient- and system-level factors. A cross-sectional analytical study was conducted between July 2023 and August 2024 across general and community hospitals. A total of 740 participants were selected using multi-stage sampling, comprising 400 older adult patients and 340 healthcare professionals. Data were collected from medical records and structured questionnaires. Descriptive statistics and multiple logistic regression were applied to identify factors linked to ED re-attendance within 60 days. Among older adults, 35% revisited the ED within 60 days post-discharge. Key factors significantly associated with re-attendance included prior ED visits (OR = 3.92; 95% CI: 2.11-7.31), hospitalization within the previous year (OR = 1.97; 95% CI: 1.15-3.38), no follow-up with specialists (OR = 2.27; 95% CI: 1.35-3.83), and treatment at M2-level hospitals (OR = 7.28; 95% CI: 3.62-14.64). Targeted strategies to improve discharge processes, ensure specialist follow-up, and enhance primary care coordination are essential to reduce potentially avoidable ED re-attendance among older adults.